The Influence of Work Motivation and Discipline on Employee Performance at PT. Kereta Api Property Manajemen Palembang - Marina Yunita; Susi Handayani; Azra’ie K. Rosni (International Journal of Marketing & Human Resource Research, 2023)
This study aims to determine the effect of motivation and work discipline on employee performance at PT. Kereta Api Property Manajemen Palembang. The type of research used in this study is associative. Population in this research all employees of PT. Kereta Api Property Manajemen Palembang. Base Hall which amounted to 110 and the sample used in this study as many as 86 respondents with sampling technique proportionate stratified random sampling. The data analysis technique used in this research is multiple linear regression analysis, F test and t test. The test result using multiple linear regression analysis simultaneously shows positive and significant influence between motivation and work discipline with Fcount 89.105> Ftable 3.11. While the partial motivation has a positive and significant effect on employee performance with the value of t 3.947> ttale 1.66365 and work discipline has a positive and significant impact on employee performance with the value of t 7.832> ttable 1.66365.